Value of blood flow resistance index plus Vaspin in predicting renal function in patients with type 2 diabetic nephropathy - Wen-qi Lu; Yan-ru Zhao; Huan-di Li; Xin-na Fan; Ping Li; Kun Wei (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the value of blood flow resistance index of both kidneys plus visceral adipose tissue-derived serine protease inhibitor (Vaspin) in predicting renal function in patients with type 2 diabetic nephropathy (T2DN). Methods From August 2021 to August 2022, 108 T2DN patients were recruited. Color ultrasonography was performed after admission for measuring renal indices. They were divided into two groups of elevated blood flow resistance index (n=40) and normal renal index (n=68). Serum level of Vaspin was detected by MeAP immunosorbent assay. The relevant clinical data were recorded. The risk factors affecting an elevation of renal indices were analyzed by univariate and multivariate Logistic regression. Pearson's method was employed for examining the relationship between renal indices, Vaspin and renal function. Receiver operating characteristic (ROC) curve was plotted according to renal indices and Vaspin. And the area under the curve (AUC) was utilized for evaluating its predictive value of renal function in T2DN patients. Results No significant inter-group differences existed in gender, stage of diabetic kidney disease, quantitative urinary protein, blood albumin, glycosylated hemoglobin, blood uric acid, urinary albumin to creatinine ratio, urinary α1 microglobulin or urinary β2 microglobulin (P>0.05). Age [(56.33±5.19) year vs (50.78±5.24) year], duration of diabetes [(12.58±3.42) years vs (10.13±3.25) years] and hypertension (87.50% vs 61.76%) were higher in elevated renal blood flow resistance index group than those in normal group. Triglyceride [(1.72±0.45) mmol/L vs (2.11±0.58) mmol/L], low-density lipoprotein (LDL) [(2.33±0.57) mmol/L vs (2.61±0.62) mmol/L], hemoglobin [(102.39±21.64) g/L vs (113.76±28.45) g/L], left kidney volume [(76.58±15.33) cm3 vs (81.35±17.16) cm3], right kidney volume [(71.62±12.39) cm3 vs (80.47±16.51) cm3], estimated glomerular filtration rate (eGFR) [(40.37±12.58) mL·min−1·(1.73 m2)−1 vs (52.14±13.26) mL·min−1·(1.73 m2)−1] and serum level of Vaspin [(1.52±0.38) μg/L vs (1.74±0.43) μg/L] were lower than those in normal group (P<0.05). Pearson's correlation analysis revealed that renal blood flow resistance index was correlated negatively with LDL, eGFR and serum level of Vaspin (P<0.05) and positively with serum creatinine and urinary albumin-to-creatinine ratio (P<0.05). Multivariate Logistic regression analysis showed that age ≥55 years (OR=1.061, 95%CI: 1.036-1.086), elevated serum creatinine (OR=1.012, 95%CI: 1.004-1.020) and higher estimated glomerular filtration rate (OR=1.037, 95%CI: 1.007-1.068) and lowered serum Vaspin (OR=1.132, 95%CI: 1.053-1.217) were independent risk factors for elevated renal blood flow resistance index (P<0.05). The area under the curve (AUC) of birenal blood flow resistance index plus Vaspin predicted renal function progression in T2DN patients was 0.79 with a sensitivity of 82.49% and a specificity of 68.73%. Conclusions Elevated blood flow resistance index in both kidneys and lower serum level of Vaspin are independent risk factors affecting renal function. A combined detection of both has an excellent predictive value for the progression of renal function in T2DN patients.